BILINGUALISM: UNLOCKING THE POWER OF TWO LANGUAGES FOR COGNITIVE AND CULTURAL GROWTH - Tolibova Ziyodaoy Nodirjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Bilingualism, the remarkable ability to communicate fluently in two languages, opens doors to unique cognitive, social, and cultural advantages. This paper delves deeply into how bilingualism enhances mental flexibility, problem-solving skills, and cultural awareness. It explores the fascinating processes of acquiring two languages, the dynamic practice of code-switching, and the profound impact on personal identity. Additionally, the study highlights the educational benefits and challenges faced by bilingual individuals. Through a comprehensive review of theories and research, this paper aims to captivate readers by revealing the transformative power of bilingualism in today’s interconnected world.